Reliability and validity of the English and Malay versions of the Driving and Riding Questionnaire: a pilot study amongst older car drivers and motorcycle riders. (February 2018) - Ang, B.H.; Chen, W.S.; Ngin, C.K.; Oxley, J.A.; Lee, S.W.H.
Abstract: Objectives: This study aimed to examine the reliability and validity of the English and Malay versions of the Driving and Riding Questionnaire. Study design: An observational study with a mix-method approach by utilising both questionnaire and short debriefing interviews. Methods: Forward and backward translations of the original questionnaire were performed. The translated questionnaire was assessed for clarity by a multidisciplinary research team, translators, and several Malay native speakers. A total of 24 subjects participated in the pilot study. Reliability (Cronbach's alpha) and validity (content validity) of the original and translated questionnaires were examined. Results: The English and Malay versions of the Driving and Riding Questionnaire were found to be reliable tools in measuring driving behaviours amongst older drivers and riders, with Cronbach's alpha of 0.9158 and 0.8919, respectively. For content validity, the questionnaires were critically reviewed in terms of relevance, clarity, simplicity, and ambiguity. The feedback obtained from participants addressed various aspects of the questionnaire related to the improvement of wordings used and inclusion of visual guide to enhance the understanding of the items in the questionnaire. This feedback was incorporated into the final versions of the English and Malay questionnaires. Conclusion: The findings of this study demonstrated both the English and Malay versions of the Driving and Riding Questionnaire to be valid and reliable. Highlights: There is an urgent need to develop an instrument that incorporates local language and culture, in identifying the determinants of self-regulatory driving or riding behaviour amongst older drivers and riders in Malaysia. The outcomes of this study demonstrated both English and Malay versions of Driving and Riding Questionnaire to be reliable and valid. The Malay version of Driving and Riding Questionnaire can be used to facilitate future studies related to driving or riding behaviours amongst older drivers and riders in Malaysia.